Relevansi Kurikulum Cinta dalam Mengatasi Krisis Moral Peserta Didik - Eti Fatiroh; Sukhoiri Sukhoiri (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This article discusses the relevance of the Love Curriculum as a conceptual framework for Islamic education curricula in responding to the moral crisis among students. The moral crisis is characterized by the weakening of ethical behavior, empathy, and social responsibility among students, which is closely related to the dominance of educational practices oriented toward cognitive achievement and academic performance, while affective and spiritual dimensions are not systematically integrated. This study aims to conceptually analyze the position and contribution of the Love Curriculum as an alternative approach to the development of Islamic education curricula grounded in the values of compassion. The research employs a library research approach with a descriptive-analytical design, using academic books and relevant national and international journal articles as data sources. Data analysis was conducted through stages of in-depth reading, data reduction, conceptual categorization, and thematic interpretation of 18 selected key literatures. The findings indicate that the Love Curriculum does not merely function as normative moral reinforcement but is constructed as an integrative curriculum framework based on the principles of rahmah (compassion), role modeling (uswah), and value habituation. The Love Curriculum emphasizes humanistic pedagogical relationships, the creation of a safe and meaningful learning environment, and the systematic internalization of Islamic values within educational goals, learning processes, and school culture. This study contributes theoretically to enriching the discourse on the development of Islamic education curricula that are humanistic, value-oriented, and responsive to students’ moral crises